2020
DOI: 10.3233/jad-191111
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and High-Density Lipoprotein Cholesterol Are Differently Associated with Alzheimer’s Disease and Vascular Dementia

Abstract: Uric acid (UA) is a major contributor to naturally-occurring antioxidant activity and is thought to have protective effects against neurodegenerative processes. However, UA is also implicated as a risk factor in vascular, including cerebrovascular, disease. Its association with, and role in, dementia and its component diseases including Alzheimer's disease (AD) and vascular dementia (VaD) remains unclear and inconsistently studied. Changes in blood lipids, particularly cholesterol measures, have also been impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…There were a smaller proportion of current smokers in the agricultural workers with PD which did not reach statistical significance. UA was found to be reduced in the PD group (286 ± 83 µmol/L) in comparison with both the VD sample (361 ± 113 µmol/L; F = 19.92, p < 0.001) and a previously studied (Liu et al 2020) and approximately agematched (62.5 ± 10.3 years; n = 79) healthy control sample (348 ± 86 µmol/L; F = 31.12, p < 0.001), controlling for age and sex. UA concentrations were lower in agricultural workers in both PD and VD samples (Table 1).…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…There were a smaller proportion of current smokers in the agricultural workers with PD which did not reach statistical significance. UA was found to be reduced in the PD group (286 ± 83 µmol/L) in comparison with both the VD sample (361 ± 113 µmol/L; F = 19.92, p < 0.001) and a previously studied (Liu et al 2020) and approximately agematched (62.5 ± 10.3 years; n = 79) healthy control sample (348 ± 86 µmol/L; F = 31.12, p < 0.001), controlling for age and sex. UA concentrations were lower in agricultural workers in both PD and VD samples (Table 1).…”
Section: Resultsmentioning
confidence: 49%
“…Data from a previously studied sample (Liu et al 2020) of 124 patients meeting diagnostic criteria for VD, including mixed dementia, were used for comparison of UA results and their relationship with agricultural work. Details of recent admissions to the hospital neurology department were used for comparison with the proportion of agricultural workers in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In a recent study, Liu et al came to the same conclusion that a lower level of uric acid is associated with AD in Chinese. 37 In our study, we analysed the AD subgroup of dementia and found that gout can reduce the risk of AD. This may also confirm the neuroprotective role of uric acid.…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have investigated the impact of individual cardiovascular risk factors, including old age, diabetes, hypertension, smoking, and hypercholesterolemia on dementia risk, and have shown inconsistent results 3–8 . Given that these cardiovascular risk factors tend to cluster and interact in an individual, 9 a multivariate risk prediction algorithm incorporating these risk factors is preferable to examine the overall impact of cardiovascular risk burden on dementia.…”
Section: Introductionmentioning
confidence: 99%